Stages of behaviour change and nutritional status regarding fruit and vegetable consumption among schoolchildren from Colombia: The fuprecol study (2017)
This article describes the relationship between stages of behavioural change regarding fruit and vegetable consumption with nutritional status among 1,922 schoolchildren (54.3% girls) from Bogotá, Colombia. A self-administered questionnaire called Behavioural Lifestyle Changes (FUPRECOL) was applied. BMI was used to categorize nutritional status. We found that 46.6% of girls and 45.4% of boys reported compliance with the daily recommendation for fruits, while 39.0% of girls and 40.4% of boys reported compliance with the daily recommendation for vegetables (p less than 0.05). Overall, overweight/obese schoolchildren showed higher frequency of not meeting the minimum recommended number of daily fruits/vegetables (precontemplation + contemplation stage) than normal weight children. Binary logistic regression showed that being a girl was associated with compliance with the minimum recommendation for fruit and vegetables (OR 1.54: 1.22-1.93, 95%CI; and OR 1.48; 1.19-1.84, 95%CI), respectively. In conclusion, around 2/3 of the participants intend or comply to consume the recommended quantities of fruit and vegetables. © 2017, Sociedad Chilena de Nutricion Bromatologia y Toxilogica. All rights reserved.